Elevated IL‐8, TNF‐α, and MCP‐1 in men with metastatic prostate cancer starting androgen‐deprivation therapy (ADT) are associated with shorter time to castration‐resistance and overall survival. Issue 8 (26th March 2014) - Sharma, Jaya; Gray, Kathryn P.; Harshman, Lauren C.; Evan, Carolyn; Nakabayashi, Mari; Fichorova, Raina; Rider, Jennifer; Mucci, Lorelei; Kantoff, Philip W.; Sweeney, Christopher J.
<x xml:space="preserve">Abstract</x> BACKGROUND Chemokines and cytokines have been implicated in progression to castration‐resistant prostate cancer (CRPC). METHODS Retrospective data were accessed from 122 men with serum samples drawn at a median of 0.5 months after starting ADT for metastatic prostate cancer. MCP‐1, IL‐1‐β, IL‐2, IL‐8, IL‐6, and TNF‐α levels were measured by multiplex electrochemiluminescence assays. A multivariable Cox model assessed the association of time to CRPC and overall survival by the protein levels and adjusted for clinical variables (age and prostate specific antigen (PSA) levels at start of ADT, race, ECOG status, and extent of metastases). Associations were reported as hazard ratio (HR) with 95% confidence interval (CI). RESULTS Median follow‐up and overall survival were 44 and 42.2 months, respectively. ECOG performance status (≥1 vs. 0) was negatively associated with overall survival [HR = 2.8 (1.1–7.0), P = 0.03], and PSA nadir < 0.2 was predictive of longer time to development of CRPC [HR = 0.3 (0.2–0.5), P < 0.0001]. The HR for time to CRPC by protein above the median was 1.4 (95% CI: 0.9, 2.2, P = 0.13) for IL‐8; 1.3 (95% CI: 0.8, 2, P = 0.18) for TNF‐α; 1.0 (95% CI: 0.7, 1.6, P = 0.95) for MCP‐1. The HR for median overall survival for protein levels above the median was: 1.9 (95% CI: 1.0, 3.5, P = 0.04) for IL‐8; 2.0 (95% CI: 1.1, 3.5, P = 0.02) for TNF‐α; 1.7 (95% CI: 1.7, 3.0, P = 0.08) for MCP‐1. There was no association with IL‐1‐β, IL‐2, or IL‐6. CONCLUSION Higher levels of inflammation‐associated cytokines correlate with poorer prostate cancer outcomes and may guide strategies to improve prostate cancer therapy. Prostate 74:820–828, 2014. © 2014 Wiley Periodicals, Inc.